Omphalocele: from diagnosis to growth and development at 2 years of age. Issue 1 (21st March 2018) - Hijkoop, Annelieke; Peters, Nina C J; Lechner, Rosan L; van Bever, Yolande; van Gils-Frijters, Annabel P J M; Tibboel, Dick; Wijnen, René M H; Cohen-Overbeek, Titia E; IJsselstijn, Hanneke
Abstract : Objectives: To compare the prenatal frame of reference of omphalocele (ie, survival of fetuses) with that after birth (ie, survival of liveborn neonates), and to assess physical growth and neurodevelopment in children with minor or giant omphalocele up to 2 years of age. Design: We included fetuses and neonates diagnosed in 2000–2012. Physical growth (SD scores, SDS) and mental and motor development at 12 and 24 months were analysed using general linear models, and outcomes were compared with reference norms. Giant omphalocele was defined as defect ≥5 cm, with liver protruding. Results: We included 145 fetuses and neonates. Of 126 (87%) who were diagnosed prenatally, 50 (40%) were liveborn and 35 (28%) survived at least 2 years. Nineteen (13%) neonates were diagnosed after birth. Of the 69 liveborn neonates, 52 (75%) survived and 42 children (81% of survivors) were followed longitudinally. At 24 months, mean (95% CI) height and weight SDS were significantly below 0 in both minor (height: −0.57 (−1.05 to –0.09); weight: −0.86 (−1.35 to –0.37)) and giant omphalocele (height: −1.32 (−2.10 to –0.54); weight: −1.58 (−2.37 to –0.79)). Mental development was comparable with reference norms in both groups. Motor function delay was found significantly more often in children with giant omphalocele (82%) than in those with minor omphalocele (21%, P=0.002). Conclusions: The prenatal and postnatal frames of reference of omphalocele differ considerably; a multidisciplinary approach in parental counselling is recommended. As many children with giant omphalocele had delayed motor development, we recommend close monitoring of these children and early referral to physical therapy.